A Review on Growth Factor Loaded Scaffolds for Rapid Healing of Bone Tissue: Life Sciences -Biotechnology - Boddepalli, Yochana; Chava, Nikhitha; Gadiraju, Sarvani; Sri Pachchava, Kavya; Kotikalapudi, Karthik; Siddiqui, Nadeem (International Journal of Life Science and Pharma Research, 2023)
Artificial bone implants from various sources, including metals, polymers, and bio-ceramics, turned out to be extensivelyoccupied in present-day tissue engineering applications. The biomaterials provide an essential platform for the osteoblast cells tomultiply, increase, and differentiate into mature osteocytes leading to bone regeneration in the defect site. Apart from biomaterialsand cells, the other essential component in tissue engineering is growth factors. Growth factors are the biomolecules responsiblefor transformation, growth, migration, and cell crawling on the biomaterial's surface. Many growth factors like BMP (BoneMorphogenetic Protein) family, (Transforming Growth Factor Beta) TGF-β, and VEGF (Vascular Endothelial Growth Factor)exhibit a crucial role in angiogenesis, extracellular matrix (ECM) formation and transformation of fibroblasts and other stem cellsinto osteocytes aiding in bone growth. In addition, the growth factors have higher renal clearance making it tough to maintain theirlevels at the site of injury, which demands a sustained release approach. Our review aims to explore various growth factors usedin treating bone defects; the primary objective is to understand each growth factor's role in the healing process and tailor thescaffold according to the requirement. Further, in this review, we have focused on the growth factors being used, their importance,and the sustained release strategies being followed for the efficient distribution of growth factors and, thus, bone healing bycovering the use of different growth factors in conjunction with biomaterials involved in the treatment of bone tissue defects.